2008
DOI: 10.1158/1078-0432.ccr-07-4074
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluoro-2-Deoxy-Glucose Uptake Predicts Clinical Outcome in Patients with Gefitinib-Treated Non–Small Cell Lung Cancer

Abstract: Purpose: To evaluate response and survival according to 18 F-fluoro-2-deoxy-glucose uptake at presentation in patients with gefitinib-treated non^small cell lung cancer. Experimental Design: We retrospectively analyzed 84 positron emission tomography/computed tomography findings. Patient characteristics, response rates, and survivals were evaluated according to the maximum standardized uptake value (SUV) of primary tumor. The cutoff value of SUVs was obtained from receiver operating characteristic analysis. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 31 publications
(31 reference statements)
3
36
0
Order By: Relevance
“…Our results are consistent with and greatly expand on results from several smaller clinical studies of PET imaging in NSCLC patients treated with EGFR inhibitors, although none of these other studies directly compared FDG-and FLT-PET imaging (21)(22)(23)(24)39). For example, Sohn and colleagues found that an FLT-PET scan after 7 days of gefitinib treatment could predict the response to treatment in 28 nonsmokers with advanced adenocarcinoma of the lung (22).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results are consistent with and greatly expand on results from several smaller clinical studies of PET imaging in NSCLC patients treated with EGFR inhibitors, although none of these other studies directly compared FDG-and FLT-PET imaging (21)(22)(23)(24)39). For example, Sohn and colleagues found that an FLT-PET scan after 7 days of gefitinib treatment could predict the response to treatment in 28 nonsmokers with advanced adenocarcinoma of the lung (22).…”
Section: Discussionsupporting
confidence: 87%
“…For example, Sohn and colleagues found that an FLT-PET scan after 7 days of gefitinib treatment could predict the response to treatment in 28 nonsmokers with advanced adenocarcinoma of the lung (22). Sunaga and colleagues reported similar findings with FDG-PET scans at 2 and 4 weeks after treatment with gefitinib (21). Soto Parra and colleagues recently reported that FDG-PET-detected changes occurring as early as 2 days after starting erlotinib can predict response in NSCLC patients (24).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Response to treatment was assessed by 18 F-fludeoxyglucose (FDG) uptake changes and tumor growth inhibition. 18 F-FDG PET is useful for early prediction of the response to gefitinib in NSCLC (26,27). Although treatment with erlotinib produced a slight decrease in 18 F-FDG uptake, the erlotinib and silibinin combination more drastically reduced the uptake as compared with treatment with either drug alone on day 7 (Fig.…”
Section: Addition Of Silibinin To Erlotinib Inhibits Growth Of Erlotimentioning
confidence: 99%
“…b FDG-positive patients (SUVmax cutoff, 8.1) had significantly shorter OS than FDG-negative patients (HR, 5.05; 95 % CI, 2.38-10.70; p<0.001). In patients underwent chemotherapy group, there was no correlation between c ERCC-1 expression (p=0.055) and d FDG uptake (p=0.974) in predicting overall survival in these patients uptake in predicting therapy response is not yet established [23][24][25]. We have also shown in our study that ERCC-1 expression or FDG uptake predicted survival in platinumbased chemotherapy patients, but further studies are needed as our subanalysis study population was relatively small.…”
Section: Discussionmentioning
confidence: 48%